Cendekia Bitara Award recognizes & rewards excellent lecturers, researchers - UMP, PNC
Universiti Malaysia Pahang (UMP) recently held its annual Cendekia Bitara 2011 Award Night – with the theme “Metamorphosis” – to reflect the decade-long journey UMP undertook to transform the university into an excellent and creative engineering and technology academic higher institution, in support of the larger national clarion call to boost the quality of Malaysia’s tertiary education.